2016
DOI: 10.1016/j.jom.2016.03.003
|View full text |Cite
|
Sign up to set email alerts
|

A life‐cycle perspective of professionalism in services

Abstract: In this article, we develop a professional service life cycle model to describe the changes in professional work over time. We explore the drivers of these changes through an in-depth longitudinal case study of one specific professional service e Leadership in Energy & Environmental Design (LEED) consulting. We focus on understanding the evolutionary path of LEED consulting work as a result of its knowledge base, community and response to market and technological forces. Case evidence demonstrates an inherent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 72 publications
0
31
0
Order By: Relevance
“…In recent work, Lawrence et al (2016) map out this progression of professional service operations as it moves away from autonomous work towards either standardization of tasks where guidelines are feasible, or motivating professionals to align with the organizational objectives when standardization is not feasible. Another recent study has found that applying a lean orientation to professional service operation fulfills an organization's desire for control and standardization (Dobrzykowski et al, 2016).…”
Section: Professionalization In a Bureaucratic Organizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent work, Lawrence et al (2016) map out this progression of professional service operations as it moves away from autonomous work towards either standardization of tasks where guidelines are feasible, or motivating professionals to align with the organizational objectives when standardization is not feasible. Another recent study has found that applying a lean orientation to professional service operation fulfills an organization's desire for control and standardization (Dobrzykowski et al, 2016).…”
Section: Professionalization In a Bureaucratic Organizationmentioning
confidence: 99%
“…The rank-and-file professionals are relieved from the bureaucratic pressures, but must instead conform to professional hierarchy practice pressures that are defined by the professional elites. Lawrence et al (2016) relate professional elites to research physicians who coordinate standards of care which filter down to the "mass service" (rank-and-file) professionals. In this structure, standards of care emerge organically from shared knowledge networks without a central bureaucratic controller (Dobrzykowski et al, 2016;Harvey, 2016).…”
Section: Professionalization In a Bureaucratic Organizationmentioning
confidence: 99%
“…Although PSFs may have the experience and the knowledge required to produce a solution, client firms have specific and situated information about their own business challenges and requirements. Therefore, the quality of the relationships between PSFs and their clients is critical for the ability of the PSF to satisfy customers' needs, thus driving clients' willingness to work with them in future (Casidy & Nyadzayo, 2017;Lawrence et al, 2016). As PSFs routinely generate most of their revenue from repeated business and cross-selling, the willingness of clients to retain their service providers ('future cooperation') is vital for the success of PSFs (Casidy & Nyadzayo, 2017).…”
Section: Business Relationships In Psfsmentioning
confidence: 99%
“…Successful business relationships are critical to the survival and growth of firms because they must leverage other organizations' resources and capabilities to stay competitive (Bao et al, 2017;Palmatier et al, 2007). In the context of business relationships between professional service firms (PSFs) and their client firms, such relationships are often forged to leverage the expertise required to solve complex business problems (Lawrence et al, 2016;Von Nordenflycht, 2010). However, with the emergence of new PSFs, competitive intensity in the professional services sector has increased (Malhotra & Morris, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation